Modelo CAPM para la valoración de acciones de las empresas en el mercado de la construcción durante el periodo 2015 - 2020; CAPM model for the valuation of shares of companies in the construction market during the period 2015 - 2020 - Genjis Alberto Ossa González; Miriam Rojas Dominguez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– This article consisted of the application of the CAPM model on companies listed on the stock exchange of and related to the construction sector in Colombia during the period from January 1, 2015 to December 31, 2020. This research has a quantitative approach with a type of descriptive and longitudinal research. Its methodology consisted in the application of ordinary least squares to the daily volatilities of the asset based on the estimation of the betas, which mostly complied with the probabilistic values and the intercepts were not different from 0, which is consistent with the model hypothesis. As for the variables that accompany the model, the risk-free rate TFIT16240724 was chosen and the ICOLCAP index was chosen as the variable that measures the market risk. Finally obtained the results, these were evaluated, concluding that the beta coefficient is an acceptable indicator in the risk-return assessment of the asset during the period in question, however, as an estimator it is not effective, which reflects the ineffectiveness of the model.
Keywords: F65; G12; 330; CAMP; risk-free rate; MCO; beta; index